Pengaruh Keterampilan Bercocok Tanam Hydroponik Type Wick System dengan Media Botol Bekas terhadap Keterampilan Vokasional Siswa Disabilitas Intelektual Ringan di SLB C TPA Jember - Caesarita, Brenda; Udhiyanasari, Khusna Yulinda; Kismawiyati, Renalatama (JOEAI (Journal of Education and Instruction), 2024)
Addressing learning challenges and providing specialised help to all students with impairments is crucial if every child is to have equal opportunity. At SLB C TPA Jember, located on Jl. Jawa No.57 Sumbersari Jember, one of the educational goals is to help students with impairments become as independent as possible. One of them is teaching kids with disabilities marketable skills, such hydroponic farming, so they may live as independently as possible. These job-specific talents may assist disabled youth become economically independent after they finish high school and find a job or launch their own business. The primary goal of this study was to identify ways in which vocational skills might help handicapped students at SLB C TPA Jember develop more independence. This research employs quantitative and descriptive methodologies. Researchers from SLB C TPA Jember conducted the research. Observation, practical testing, and documentation were the main sources of data for this research. Putting these vocational skills programmes into reality has the full support of everyone from classroom teachers to supplemental educators to school officials. Keywords: vocational abilities, farming wick-type hydroponic system, children with special needs.